A Cohort Model of Mentoring as Facilitator to the Transition to an Academic Nurse Faculty Position Following Completion of a PhD. Issue 5 (September 2021) - Viveiros, Jennifer; Schuler, Monika; Chung, Joohyun; D'Esmond, Lynn
Abstract : Abstract: Successful transition to an academic nurse educator role is challenging; it is necessary to identify facilitators and barriers that aide or hinder this process. This study used an autoethnographic qualitative design to explore the lived experiences of a cohort of faculty during their transition into a tenure-track role. Three facilitators (noncompetitive environment, resource sharing, and cohort approach) and two barriers (work-life balance and intrusion of old habits) emerged as themes. A cohort model can be a valuable facilitator for a successful transition. Multitiered mentoring further aided in the transition.